ANALISIS KEBUTUHAN AIR BERSIH DI KELURAHAN AFA-AFA KOTA TIDORE KEPULAUAN - Syahjuan; zulkarnain; Irnawati; Yuni Damayanti (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2026)
Clean water is a basic human need that is crucial in daily life. In addition to household needs, clean water is also needed to meet the water needs of public, social, and economic facilities, in line with the increasing number of public facilities and population growth. Afa-Afa Village is an administrative area located in North Tidore District, Tidore Islands City, North Maluku Province. Afa-Afa Village has a population of 1,364. The population increase from 1,209 in 2013 to 1,364 in 2024 indicates significant growth, which has a direct impact on the increasing need for clean water. This study aims to analyze and project the total clean water needs in Afa-Afa Village, North Tidore District, Tidore Islands City in 2025 and going forward in 2034. The method used is quantitative descriptive with secondary data analysis. Population projections for 10 years were carried out by comparing Arithmetic, Geometric, and Least Squares methods, and the Least Squares method was chosen because it provided the most representative results for growth trends. Water needs were calculated based on the planning criteria of the Directorate General of Human Settlements, Department of Public Works. This calculation was then refined by considering actual data and technical assumptions. The results of the analysis show that the total clean water needs in Afa-Afa Village in 2025 with the assumption of 20% water loss is 0.4254 liters/second, and is projected to increase to 0.4642 liters/second in 2034, after taking into account domestic, non- domestic, and water losses (20%). This study concludes that water demand in Afa-Afa Village continues to increase, and the results can be used as a reference in planning and developing a clean water supply system in the area for the next 10 years.